Fish for Life Interactive Governance for Fisheries - Kooiman, Jan; Jentoft, Svein; Bavinck, Maarten; Pullin, Roger (MARE Publication Series, 2005)
One billion people around the world rely upon fish as their primary-and in many cases, their only-source of protein. At the same time, increasing demand from wealthier populations in the U.S. and Europe encourages dangerous overfishing practices along coastal waters. Fish for Life addresses the problem of overfishing at local, national, and global levels as part of a comprehensive governance approach-one that acknowledges the critical intersection of food security, environmental protection, and international law in fishing practices throughout the world. Third publication in the "http://www.aup.nl/mare">MARE Publication Series